IMPROVED SEISMIC IMAGING THROUGH PETROPHYSICAL APPROACH USING THOMSEN'S PARAMETER ESTIMATION IN ANISOTROPIC PRESTACK DEPTH MIGRATION (PSDM) - Minarto, Eko; Fahmi, Muhammad; Putra, Ginanjar Satria (Universitas Mataram, 2024)
Research has been carried out using the Prestack Depth Migration (PSDM) anisotropy method for 2D reflection seismic data. This research aims to estimate anisotropic parameter values with a petrophysical approach to the Prestack Depth Migration method to obtain better imaging results. The type of anisotropic medium used is Vertical Transverse Isotropy (VTI) because that can explain the effect of anisotropy in a simple form on the sediment layer. In theory, 2 parameters are needed to describe this parameter, namely Îµ and Î´. Î´ is an anisotropic parameter that describes the velocity variation towards a nearly vertical direction and is the control depth of seismic. In contrast, Îµ describes the velocity variation towards the near horizontal direction. The stages of data processing are divided into two; the first is PSDM isotropy, which flattens gather at near offset (angle mute <30 degrees), and PSDM anisotropy to flatten-gather at far offset (mute angle> 30 degrees). The results of this study showed that the relation of Îµ and Î´ in shale formations was (Î´ = 0.4958Îµ - 0.0152) and sand formation (Î´ = 0.9082Îµ - 0.0203) and the range of anisotropic parameters Î´ and Îµ were -0.02 up to 0.13 and 0 up to 0.3. From all ranges of anisotropic parameter values, this study belongs to the